Tekening bij artikel "Doodstraf als enig middel waarmee de bloedschuld der oorlogsmisdadigers kan worden gedelgd!" - C.L.,
Tekening bij artikel "Doodstraf als enig middel waarmee de bloedschuld der oorlogsmisdadigers kan worden gedelgd!"